2018
DOI: 10.1002/acr.23448
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Performance on Clinical Tests of Physical Function to Predict Walking 6,000 Steps/Day in Knee Osteoarthritis: An Observational Study

Abstract: Not meeting these minimum performance thresholds on clinical tests of physical function may indicate inadequate physical ability to walk ≥6,000 steps/day for people with knee OA. Rehabilitation may be indicated to address underlying impairments limiting physical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Master et al . 24 ) reported 10.5±2.9 s as the FTSST time for 1925 patients with knee OA (1065 women, mean age 65.1±9.1 years), and Bohannon et al . 25 ) showed that FTSST times in community-dwelling elderly people were 8.1±3.1 s in individuals aged 60–69 years, 10.0±3.1 s in individuals aged 70–79 years, and 10.6±3.4 s in individuals aged 80–89 years, and these times are used as reference values.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Master et al . 24 ) reported 10.5±2.9 s as the FTSST time for 1925 patients with knee OA (1065 women, mean age 65.1±9.1 years), and Bohannon et al . 25 ) showed that FTSST times in community-dwelling elderly people were 8.1±3.1 s in individuals aged 60–69 years, 10.0±3.1 s in individuals aged 70–79 years, and 10.6±3.4 s in individuals aged 80–89 years, and these times are used as reference values.…”
Section: Discussionmentioning
confidence: 96%
“…This study determined that changes exceeding 1.71 s in the FTSST time are changes in clinically meaningful that exceed the measurement error. Master et al 24) reported 10.5±2.9 s as the FTSST time for 1925 patients with knee OA (1065 women, mean age 65.1±9.1 years), and Bohannon et al 25) showed that FTSST times in community-dwelling elderly people were 8.1±3.1 s in individuals aged 60-69 years, 10.0±3.1 s in individuals aged 70-79 years, and 10.6±3.4 s in individuals aged 80-89 years, and these times are used as reference values. It is important to interpret these values by comparing them with the reference values in previous studies to accurately grasp the decline in the standing ability of patients with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger study of the OA-PCP intervention, we plan to provide participants with activity trackers to facilitate self-monitoring. The goal-setting component of the OA-PCP intervention will also be modified so that participants are guided to choose goals specific to either step counts or minutes of MVPA, with long-term goals based on recent evidence for reducing risk of functional decline in OA [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, a threshold created from a heterogeneous group will likely represent varying degrees of physical function limitations depending on a patient's characteristics. Figure 2 illustrates how a common walking speed threshold of 1.22 m/s reflects different relative levels of objective physical function (determined by our reference value tables) that considers each combination of sex with age, radiographic KOA severity, and BMI [30,45]. For example, a female with a walking speed of 1.22 m/s represents the 34th percentile when compared to all females within our cohort, indicating they walk faster than 34% of the females in the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals unable to complete the single or repeated chair stand test due to functional limitations were assigned a 0 chair stands/min speed [28]. 400-m walk time-Among those who could complete the 20-m walk test, participants performed one timed 400-m walk trial, while being instructed to "pace themselves without overexertion" as a measure of walking endurance [30]. The participants walked 20-m to a cone, walked around the cone, then back 20-m to a starting cone.…”
Section: Objective Physical Function Testsmentioning
confidence: 99%